Development and Treatments of Inflammatory Cells and Cytokines in Spinal Cord Ischemia-Reperfusion Injury - Ping Zhu; Jia-xin Li; Masayuki Fujino; Jian Zhuang; Xiao-Kang Li (Mediators of Inflammation)
During aortic surgery, interruption of spinal cord blood flow might cause spinal cord ischemia-reperfusion injury (IRI). The incidence of spinal cord IRI after aortic surgery is up to 28%, and patients with spinal cord IRI might suffer from postoperative paraplegia or paraparesis. Spinal cord IRI includes two phases. The immediate spinal cord injury is related to acute ischemia. And the delayed spinal cord injury involves both ischemic cellular death and reperfusion injury. Inflammation is a subsequent event of spinal cord ischemia and possibly a major contributor to spinal cord IRI. However, the development of inflammatory mediators is incompletely demonstrated. And treatments available for inflammation in spinal cord IRI are insufficient. Improved understanding about spinal cord IRI and the development of inflammatory cells and cytokines in this process will provide novel therapeutic strategies for spinal cord IRI. Inflammatory cytokines (e.g., TNF-α and IL-1) may play an important role in spinal cord IRI. For treatment of several intractable autoimmune diseases (e.g., rheumatoid arthritis), where inflammatory cytokines are involved in disease progression, anti-inflammatory cytokine antagonist is now available. Hence, there is great potential of anti-inflammatory cytokine antagonist for therapeutic use of spinal cord IRI. We here review the mediators and several possibilities of treatment in spinal cord IRI.